2002
DOI: 10.1002/dev.10023
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ethanol exposure and spatial navigation: Effects of postnatal handling and aging

Abstract: Prenatal ethanol exposure results in spatial navigation deficits in young and mid-aged animals. In contrast, postnatal handling attenuates spatial deficits that emerge with age in animals that are not handled. Therefore, we investigated the ability of handling to attenuate spatial deficits in animals prenatally exposed to ethanol (E). Sprague-Dawley male offspring from E, pair-fed (PF), and control (C) groups were handled (H) or nonhandled (NH) from 1 to 15 days of age and tested on the Morris water maze at 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 82 publications
1
17
0
Order By: Relevance
“…In utero ethanol exposure or neonatal exposure during the brain growth spurt induces numerous cognitive and behavioral deficits. Of relevance to the current study are findings of impaired spatial learning and memory in the offspring (Blanchard et al, 1987;Kelly et al, 1988;Gianoulakis, 1990;Kim et al, 1997;Gabriel et al, 2002;Richardson et al, 2002;Savage et al, 2002;Iqbal et al, 2004;Christie et al, 2005), with animals exhibiting deficits similar to those observed following bilateral lesions of the hippocampus (Morris et al, 1982). In addition, long-term potentiation (LTP), a biological model for learning and memory processes, is also impaired in E animals (Sutherland et al, 1997;Richardson et al, 2002;Savage et al, 2002;Christie et al, 2005).…”
Section: Introductionmentioning
confidence: 65%
“…In utero ethanol exposure or neonatal exposure during the brain growth spurt induces numerous cognitive and behavioral deficits. Of relevance to the current study are findings of impaired spatial learning and memory in the offspring (Blanchard et al, 1987;Kelly et al, 1988;Gianoulakis, 1990;Kim et al, 1997;Gabriel et al, 2002;Richardson et al, 2002;Savage et al, 2002;Iqbal et al, 2004;Christie et al, 2005), with animals exhibiting deficits similar to those observed following bilateral lesions of the hippocampus (Morris et al, 1982). In addition, long-term potentiation (LTP), a biological model for learning and memory processes, is also impaired in E animals (Sutherland et al, 1997;Richardson et al, 2002;Savage et al, 2002;Christie et al, 2005).…”
Section: Introductionmentioning
confidence: 65%
“…We did not use cross-fostering because dams in our model show no signs of malnutrition compared with normal (12,14). Furthermore, it has been suggested that fostering may confound the effects of prenatal EtOH exposure (28). Because of similar litter sizes between groups, we also refrained from culling pups as litter size manipulation has been shown to alter neuronal activity and the level of nutrition received during lactation (20).…”
Section: Methodsmentioning
confidence: 99%
“…Neonatal handling during the first 3 weeks, which involved daily separation from home cages and tactile stimulation, was effective in eliminating this learning deficit. Researchers have failed, however, to eliminate spatial memory deficits in alcoholexposed animals through neonatal handling (Gabriel et al 2002). Gabriel et al (2000) have also reported that neonatal handling was ineffective at ameliorating hypothalamicpituitary-adrenal hyperresponsiveness to stress and at normalizing hypothalamic corticotropin-releasing factor levels in alcohol-exposed animals.…”
Section: Neonatal Handlingmentioning
confidence: 96%